2015
DOI: 10.25103/jestr.083.25
|View full text |Cite
|
Sign up to set email alerts
|

A review on location, detection and fault diagnosis in induction machines

Abstract: In this work a careful review describing different types of failures in electrical machines, their characteristic signals generated and diagnosis methods is performed. Additionally, a comparison of the advantages between the known failure detection methods based on the information required for diagnosis, the occurrence and importance of failures detection, the effectiveness for anticipating a malfunction or failure and the final diagnosis accuracy is also made. Particularly, this review will help to provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Review papers presented in Refs. [158][159][160][161][162][163] on the condition monitoring techniques for the induction motors demonstrate that extensive research has been carried out in the last decade on the development of a non-invasive condition monitoring system for diagnosis of gear defects and bearing localized faults. It has been found that the mechanical vibration produce characteristic frequencies in stator current spectrum.…”
Section: Condition Monitoring Issuesmentioning
confidence: 99%
“…Review papers presented in Refs. [158][159][160][161][162][163] on the condition monitoring techniques for the induction motors demonstrate that extensive research has been carried out in the last decade on the development of a non-invasive condition monitoring system for diagnosis of gear defects and bearing localized faults. It has been found that the mechanical vibration produce characteristic frequencies in stator current spectrum.…”
Section: Condition Monitoring Issuesmentioning
confidence: 99%
“…This technique was named motor current analysis (MCA). 3034 Several papers have been published in the past decade to improve the performance of the MCA by developing pre-processing algorithms to make the condition monitoring system reliable, efficient, economical, and to reduce the complexity. 3538 Although MCA is a better alternative to intrusive techniques but harmonics associated with defects are suppressed by the amplitude of line frequency and give a false alarm.…”
Section: Introductionmentioning
confidence: 99%